Problemáticas étnicas y sociales desde el pensamiento latinoamericano Temas, Conceptos, Enfoques - Kozel, Andrés; Rawicz, Daniela; Devés, Eduardo (Ariadna Ediciones, 2023)
This work is the second volume of a series that looks more extensive. His direct antecedent is the book International and World Problems from the Latin American Thought, edited by Eduardo Devés and Silvia T. Álvarez, and published in 2020 by this same publishing label. The main objective of the series is to help undergraduate and postgraduate have a material that helps them to know and recognize the contributions of the Latin American thought to different sets of issues and problems. Of course, the knowledge that is produced in our region must be problematized and made available.